2023
DOI: 10.4149/gpb_2022054
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0001498 contributes to lipopolysaccharide-induced lung cell apoptosis and inflammation in sepsis-related acute lung injury via upregulating SOX6 by interacting with miR-574-5p

Abstract: Circular RNAs (circRNAs) have important regulation in in sepsis-related acute lung injury (ALI). Circ_0001498 was significantly overexpressed in sepsis-induced acute respiratory distress syndrome. The aims of this study were to explore role and mechanism of circ_0001498 in lipopolysaccharide (LPS)-treated WI-38 cells. Human samples were collected from 56 sepsis patients and 46 healthy volunteers at Liyang People's Hospital. Circ_0001498, microRNA-574-5p (miR-574-5p) or sex-determining region Y-related high-mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It was identified as sepsis-associated miRNA, and downregulation of its levels can predict the development of acute kidney injury in patients with sepsis [ 35 ]. MiR-574-5p was significantly reduced in acute lung injury associated with sepsis [ 36 ] and was recognized as a miRNA associated with death in patients with sepsis [ 37 ]. Consistent with previous studies, we also found that miR-574-5p levels were generally lower in patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…It was identified as sepsis-associated miRNA, and downregulation of its levels can predict the development of acute kidney injury in patients with sepsis [ 35 ]. MiR-574-5p was significantly reduced in acute lung injury associated with sepsis [ 36 ] and was recognized as a miRNA associated with death in patients with sepsis [ 37 ]. Consistent with previous studies, we also found that miR-574-5p levels were generally lower in patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the in-silico study we performed showed that miR-574 is not significantly associated with any of the four cancer-related pathways. Therefore, the results of a recent study by Wei et al seem to be more interesting [ 37 ]. These researchers discovered a mechanism of circ_0001498 action that stimulates sepsis-induced acute lung failure syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al found that overexpression of circ_0001498 mediated by miR-574 upregulates SOX6 . In contrast, overexpression of miR-574 had the opposite effect (downregulation of SOX6 ), resulting in attenuation of cell damage [ 37 ]. The effect of the increased miR-574 expression on attenuating sepsis-induced lung injury was also confirmed in another study [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A range of types of programmed cell death has been confirmed to play a pivotal role in the development of sepsis-induced ARDS; the representative ones include circ_0001498/miR-574-5p/SOX6 axis-involved apoptosis, bleb formation to epithelial cells necrosis, Sirtuin 6-regulated alveolar macrophages autophagy, Mucin 1/keap-1-involved ferroptosis, and Gasdermin D (GSDMD)-dominant pyroptosis, among which pyroptosis has been received most in-depth investigation. Pyroptotic cell death is a double-edged sword since it released pro-inflammatory mediators to gather the nearby immune cells around the pathogenic infected sites and subsequently destroy their replication niches and enhance adaptive immune responses.…”
Section: Pyroptosis Plays a Central Role In The Pathophysiology Of Se...mentioning
confidence: 99%